Phytoremediation of Nickel via Water Hyacinth for Biocarbon‐Derived Supercapacitor Applications. Issue 8 (30th June 2021) - Shell, Katelyn M.; Vohra, Shaan Y.; Rodene, Dylan D.; Gupta, Ram B.
Abstract : Water hyacinth ( Eichhornia crassipes, WH) is cultivated in a hydroponic system containing various concentrations of Ni 2+ to demonstrate phytoremediation techniques as a facile, low‐cost, and sustainable method for synthesizing high‐performance biocarbon electrode materials. A high specific capacitance of 541 F g −1 in 2 m potassium hydroxide (KOH) is achieved for WH‐5 biocarbon with an energy density of 30.5 Wh kg −1 . Materials are assembled into a coin cell supercapacitor capable of lasting 10 000 cycles with 100% capacitance retention. Surface area characterizations support these results with an S BET of 3429 m 2  g −1, a V BET of 2.13 cm 3  g −1, and an S p avg of 2.5 nm, indicating enhanced pore formation and functional group cleaving. Raman spectroscopy, attenuated total reflectance Fourier transform IR (ATR‐FTIR), and X‐ray diffraction (XRD) give further insight into physical characteristics of the biocarbon that lead to improved electrochemical performance. This work describes an optimal concentration of preabsorbed Ni 2+ catalyst (5 ppm in H2 O) capable of achieving 98% of theoretical capacitance and value‐added environmental cleanup associated with synergistic remedial techniques. Abstract : Water hyacinth as a hyperaccumulator of nickel is utilized as a bio‐mass precursor for use in producing supercapacitor electrodes. A high specific capacitance of 541 F g −1 is achieved in 2 m potassium hydroxide with 100% capacitance retention after 10 000 cycles. The method provides a sustainable approach for obtaining biocarbon while carrying out bioremediation.